SAT0509 MYCOPHENOLATE MOFETIL VERSUS AZATHIOPURINE FOR THE MAINTENANCE TREATMENT OF CONNECTIVE-TISSUE RELATED INTERSTITIAL LUNG DISEASE FOLLOWING CYCLOPHOSPHAMIDE TREATMENT. (2nd June 2020) - Satiş, H.; Onut, M.; Bilici Salman, R.; Babaoglu, H.; Atas, N.; Avanoğlu Güler, A.; Karadeniz, H.; Yapar, D.; Kayahan, N.; Haznedaroglu, S.; Goker, B.; Ozturk, M. A.; et al.
Abstract : Background: Cyclophosphamide (CYC) had a good response rates when used as an induction regimen for the treatment of connective tissue related interstitial lung disease (CTD-ILD). But the safety profile of CYC necessitates the usage of a second line treatment for maintenance Objectives: To compare the effect of mycophonetil (MMF) and azatiyopurin (AZA) for maintanance therapy following cyclophsphomide treatment in CTD-ILD Methods: Between 2009 and 2019 all interstitial lung disease patients admitting rheumatology or pulmonology department were retrospectively evaluated and patients treated with cyclophospamide as an induction regimen and having not progression were selected. Among those, as a second line regimen treated with MMF or AZA were included. Primary end point was treatment responses at 6th months Results: 68 patients treated with CYC for the first line treatment. 46 patients treated with either MMF (n:22) or AZA (n:24) for the maintenance. Scleroderma patients were the largest group and consituted 63% of the population. MMF group had worse FVC values and more involvement in lung paranchyme at the begining of the treatment. In univariate analysis FVC (lt) values and lung involvement (%) on HRCT at the start of the treatment, and disease subtype were associated significantly with treatment responses.After adjusted with these factors, in multivariate analysis, AZA treatment was associated with the increased risk of progression (odds ratio 5, 8, 95% CI 1, 061-31, 09) as compared with MMF treatment Conclusion: MMF had better results compared to AZA in the treatment of CTD-ILD, after the usage of CYC treatment. References: [1]Barnes, H., et al., Cyclophosphamide for connective tissue disease-associated interstitial lung disease. Cochrane Database Syst Rev, 2018. 1 (1): p. Cd010908. Disclosure of Interests: None declared